Experiências de universitários brasileiros em mobilidade acadêmica : reflexões sobre cursos e materiais didáticos em língua inglesa - Oliveira, Talita Aparecida de (2016)
International academic mobility programs have been intensified in Brazil in the last few years. In 2015, one of these initiatives, Science without Borders (SwB), achieved its goal of sending 100 thousand students for academic programs, 78% being undergraduate students. Since the beginning of this governmental action in 2011, the need for developing Brazilian students’ proficiency in English became evident, which led to the stablishment of the national program Languages without Borders (LwB) in 2013. In this research, we developed an analysis of locally produced teaching materials used in courses for students who wanted to participate in academic mobility programs in English speaking countries. These material have been designed by the local IsF team, with the participation of student teachers. Through an evaluative case study (MERRIAM, 2007), we analysed 6 undergraduate students’ experience after taking courses LwB in Brazil and becoming participants of the SwB program. Using semi-structured interviews and developing a virtual group with the participants, we analysed situations that they have experienced and identified linguistic and pragmalinguistic challenges, the latter are related to appropriate linguistic choices that the speaker makes during communicative situations (KASPE e ROSE, 2001; HINKEL, 2012). The analysis demonstrates, based on principles of teaching materials development (TOMLINSON, 2010), that the materials had a positive impact on the students’ experiences. Issues like autonomy development, extensive opportunities of listening speakers in communicative situations and study of genres were identified. This study reveals that there are aspects to be closely considered in ELT materials for exchange students, such as developing students’ awareness about communication with other speakers of English as a second language and using strategies in new environments.